Recurrent bacteraemia by 2 different Bacillus cereus strains related to 2 distinct central venous catheters - Koch, Andrea; Arvand, Mardjan (Scandinavian journal of infectious diseases, 2005)
A 14-y-old girl with osteosarcoma developed 3 episodes of catheter-related bacteraemia by Bacillus cereus. After removal of the first and insertion of a second Hickman catheter, further episodes of B. cereus bacteraemia occurred. PFGE analysis revealed that bacteraemic episodes related to each catheter were caused by a distinct B. cereus strain.
Gesehen am 07.07.2022